2021
DOI: 10.3390/ani11051388
|View full text |Cite
|
Sign up to set email alerts
|

Specific Seminal Plasma Fractions Are Responsible for the Modulation of Sperm–PMN Binding in the Donkey

Abstract: While artificial insemination (AI) with frozen-thawed sperm results in low fertility rates in donkeys, the addition of seminal plasma, removed during cryopreservation, partially counteracts that reduction. Related to this, an apparent inflammatory reaction in jennies is induced following AI with frozen-thawed sperm, as a high amount of polymorphonuclear neutrophils (PMN) are observed within the donkey uterus six hours after AI. While PMN appear to select the sperm that ultimately reach the oviduct, two mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
4
1
Order By: Relevance
“…It was previously reported that the negative impact of bacteria potentially responsible for urogenital tract infections on routine sperm quality markers is often associated with supraphysiological levels of seminal leukocytes [40][41][42][43][44][45]. A positive correlation between the bacterial load and the occurrence of leukocytes recorded in our study agrees with previous observations in animals [44,45] as well as humans [41][42][43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was previously reported that the negative impact of bacteria potentially responsible for urogenital tract infections on routine sperm quality markers is often associated with supraphysiological levels of seminal leukocytes [40][41][42][43][44][45]. A positive correlation between the bacterial load and the occurrence of leukocytes recorded in our study agrees with previous observations in animals [44,45] as well as humans [41][42][43].…”
Section: Discussionsupporting
confidence: 92%
“…While both events are inherently designed to offer protection to the sperm survival in a bacteria-infested environment, a critical moment may arise when the ETs start to have a negative effect on the sperm motility, particularly by elevating oxidative tension and by physically trapping the male gametes. While this phenomenon has been observed in humans [46,47], cattle [44], and equines [45], mutual associations between the leukocyte concentration, ROS amounts, and the impairment of the sperm motility may be indicative of the assumption that ETs may emerge in bacteriospermic avian semen as well. As such, the involvement of leukocytes in the sperm immobilization, as a result of bacterial contamination of semen, is an intriguing area worth of further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Sperm motility, judged subjectively, was considered to be lower in the presence of added seminal plasma. This result is in contrast to other studies where adding seminal plasma to fresh spermatozoa increased sperm motility ( 53 , 54 ).…”
Section: Role Of Seminal Components and Semen Extender In Persistent Endometritiscontrasting
confidence: 99%
“…The reason for decreased cooling tolerance of donkey semen containing seminal plasma in milk-based extenders is not well understood. Although recent studies on donkey seminal plasma compounds and effects have suggested an important interaction between the seminal plasma composition in donkeys and the sperm freezing ability ( 40 , 41 ), these interactions have not yet been described with regards to how well donkey sperm tolerates cooling. It has been suggested that donkey seminal plasma contains proteins that remove cholesterol from the sperm plasma membrane ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the present study demonstrated two methods to circumvent this poor ability of donkey semen to tolerate cooling (extending the semen in EY-based extender, or removing the seminal plasma and extending in SC-based extender) which achieved satisfactory pregnancy rates (74–89%) in mares ( 18 ). However, it is also essential to recognize that even though centrifugation and removal of seminal plasma have been a prevalent recommendation for cooling donkey semen ( 2 ), seminal plasma appears to play an essential role in the modulation of the endometrial response after artificial insemination in jennies ( 40 , 64 , 65 ). Seminal plasma decreases sperm binding to polymorphonuclear (PMNs) and other inflammatory cells to sperm ( 66 , 67 ), and more specifically in donkey species, seminal plasma has been described to suppress the in vitro sperm-attachment of PMNs collected from uterine secretions of jennies after artificial insemination ( 40 , 64 ), downregulate endometrial COX2 expression in jennies upon artificial insemination with frozen-thawed semen ( 68 ), induce neutrophil extracellular traps (NETs) formation ( 69 ), and increase pregnancy rates following artificial insemination with frozen-thawed semen in this species ( 70 ); even though the addition of seminal plasma to frozen-thawed donkey semen samples does not improve in vitro sperm characteristics ( 71 ).…”
Section: Discussionmentioning
confidence: 99%